From biofilm control to biomimetic remineralization: Hydrogels in prevention and treatment of dental caries - Chen, Yuqing; Lin, Shikang; Huang, Xiaojing; Zhou, Wen (Frontiers in Cellular and Infection Microbiology, 2025)
Dental caries, a prevalent chronic bacterial disease globally, poses a significant threat to public health due to its complex pathogenesis involving demineralization and microbial dysbiosis. Hydrogels, with their unique three-dimensional network structures and diverse properties, have shown great potential in prevention and treatment of dental caries. This article systematically reviews recent advances in anti-caries hydrogel development. It first introduces the basis of anti-caries hydrogels, covering the applications of natural and semi-synthetic polymers as hydrogel matrices. Then, it elaborates on the mechanisms and research status of different types of anti-caries hydrogels, including probiotic formulations, antibacterial hydrogels, remineralization-inducing hydrogels, and saliva-related caries-reducing hydrogels. Finally, it summarizes the current research achievements and limitations and looks ahead to future research directions.